Analisa Pengaruh Teknologi Informasi terhadap Kinerja Karyawan Pada PT. Sarana Mitratama Sejati Jakarta - Rafi De Putra; Leliyanah Leliyanah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
This research aims to find out whether there is a significant influence between information technology on employee performance at PT. Sarana Mitratama Sejati Jakarta. This research consists of two variables, namely information technology (independent variable or variable X) and employee performance (dependent variable or variable Y). The population in this study is all employees as many as 40 employees. Sampling in this study using a sampling technique saturated, that is, all populations in this study were used as samples.The samples used in this study were 40 employees of PT Sarana Mitratama Sejati and data collection techniques were through questionnaires.Data processing in this study used the IBM SPSS version 25 program to calculate the test validity, reliability test, classic assumption test, simple linear regression test and hypothesis testing.The test results show that information technology has a positive and significant impact on employee performance at PT Sarana Mitratama Sejati Jakarta.